Case Report: ACTH- and CRH-secreting pheochromocytoma as a very rare cause of ectopic Cushing syndrome - Bromińska, Barbara; Sawicka-Gutaj, Nadia; Szczepanek-Parulska, Ewelina; Lange-Ratajczak, Małgorzata; Wierzbicki, Tomasz; Janicka-Jedyńska, Małgorzata; Czepczyński, Rafał; Ruchała, Marek (Frontiers in Endocrinology, 2025)
Ectopic adrenocorticotropic hormone (ACTH) syndrome (EAS) represents a rare clinical entity characterized by severe hypercortisolemia. Pheochromocytoma, a neuroendocrine neoplasm originating from chromaffin cells within the adrenal medulla, is itself an uncommon diagnosis. The phenomenon of ectopic hormone production by pheochromocytomas is exceedingly rare, occurring in less than 1% of cases. In most instances, hypercortisolemia associated with pheochromocytoma is attributed to aberrant ACTH secretion. This report presents an exceptional case of EAS caused by a pheochromocytoma exhibiting co-expression of both ACTH and corticotropin-releasing hormone (CRH).